# |
ODE |
Mathematica |
Maple |
\[
{}x {y^{\prime }}^{2}-4 y^{\prime }-12 x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 5-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x
\] |
✓ |
✓ |
|
\[
{}\left (4-y^{2}\right ) y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y^{3}+1\right ) y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y-x \right ) y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 3 x -6
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y-4
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (-3+y\right )
\] |
✓ |
✓ |
|
\[
{}3 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 y-2\right ) y^{\prime } = 2 x -1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 \sqrt {y}+5 x^{3}
\] |
✗ |
✗ |
|
\[
{}y^{\prime }+y \sin \left (x \right ) = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = \frac {1}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}1+{y^{\prime }}^{2} = \frac {1}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (1-x y\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 3 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 1-x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = -x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = -x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{5}+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{5}+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-\cos \left (\frac {\pi x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-\cos \left (\frac {\pi x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (y-4\right )^{2}-2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-2\right )^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 10+3 y-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2} \left (4-y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (2-y\right ) \left (4-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \ln \left (y+2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y \,{\mathrm e}^{y}-9 y\right ) {\mathrm e}^{-y}
\] |
✓ |
✓ |
|